Hypoglycaemia and infectious gastroenteritis: the risk of sugar-free fluids. (24th May 2012) - Laraway, S; Gardner, C; Belderbos, R
Abstract : Background: The National Institute of Health and Clinical Excellence has made recommendations regarding the management of children under five with infectious gastroenteritis. This includes the use of sugar-free fluids such as water for rehydration. A local audit has demonstrated a marked increase in the incidence of hypoglycaemia in such children in recent years. Aims: To determine if provision of only sugar-free fluids to children <5 years with infectious gastroenteritis is related to hypoglycaemia at presentation. To compare the clinical characteristics of such children with and without hypoglycaemia. Patients and methods Retrospective casenote audit of acute admissions to a district general hospital between April 2010 - May 2011. 67 children (28 hypoglycaemic) <5 years diagnosed with infectious gastroenteritis were included. Children with conditions known to predispose to hypoglycaemia were excluded. Hypoglycaemia was defined as glucose of ≤3 mmol/l. Statistical significance was evaluated using fisher's exact test (p<0.05). Results: Stated as mean[range]: Age of the hypoglycaemic children was 1.5 [0.1-3.4] years and 1.6 [0.2-4.5] years in the non-hypoglycaemic group. Vomiting as a presenting symptom was associated with hypoglycaemia. Duration of illness was not. Clinical features associated with hypoglycaemia were drowsiness and subjective assessment of looking 'unwell'. Dry mucous membranes, reduced skin turgor, tachycardia, sweatiness and pallor were not associated with hypoglycaemia. In twenty cases, stool culture and virology were sent. Six were positive for rotavirus: all were hypoglycaemic. Three were positive for campylobacter: none were hypoglycaemic. Of the other eleven, only two were hypoglycaemic. The fluids given at home were documented in 40/67 cases (60%). There was an association between giving only sugar-free fluids at home and documented hypoglycaemia (p=0.05). When only children with a measured sugar were considered, 1/11 (9%) of normoglycaemic children had sugar-free fluids compared with 6/15 (40%) of those who were hypoglycaemic, but this difference did not reach statistical significance. Conclusion: Provision of only sugar-free drinks at home was associated with hypoglycaemia at presentation, as was the presence of vomiting. Longer duration of illness was not. Hypoglycaemia at presentation was associated with rotavirus infection.